Serum α1-AT Levels and SERPINA1 Molecular Analysis in Breast Cancer: An Experimental and Computational Study - Guadalupe Ávalos-Navarro; Luis A. Bautista-Herrera; Asbiel Felipe Garibaldi-Ríos; Ramiro Ramírez-Patiño; Marisol Gutiérrez-García; Perla Briseño-Álvarez; Luis Felipe Jave-Suárez; Emmanuel Reyes-Uribe; Martha Patricia Gallegos-Arreola (Diseases)
Background/Objectives: Breast cancer (BC) is a heterogeneous disease with multifactorial origins, including environmental, genetic, and immunological factors. Inflammatory cytokines, such as alpha 1 antitrypsin (α1-AT), are increased in BC and affect physiological and pathological conditions. This study aimed to evaluate the serum levels of α1-AT and perform a computational analysis of SERPINA1 in BC, as well as their association with molecular subtypes and clinical features. Methods: For the experimental analysis, we evaluated 255 women with BC and 53 healthy women (HW) in a cross-sectional study. Molecular subtypes were identified by immunohistochemistry and TNM was used for clinical staging. Soluble levels of α1-AT were quantified by ELISA. Computational analysis of SERPINA1 expression was performed using GEPIA and cBioPortal. Results: α1-AT was increased in BC women versus HW (75.8 ng/mL vs. 532.2 ng/mL). Luminal A had higher concentration (547.5 ng/mL) than Triple Negative (TN) (484.1 ng/mL), but the levels were not associated with clinical stage. The computational analysis showed that SERPINA1 is overexpressed in BC with differential expression among subtypes; its overexpression is associated with a better prognosis, longer disease-free survival, and overall survival. Conclusions: α1-AT levels are increased in women with BC women compared to HW. The Luminal A subtype shows higher soluble protein levels than the TN one. Furthermore, SERPINA1 mRNA overexpression in BC is linked to a protective effect.